Level of Utilizing New Media in Spreading Security Awareness among Students of Palestinian Universities in the Governorates of Southern Palestine - Dr. Mahmoud A.R. Assaf; Wael M. H. Koraz (University of Science and Technology, Yemen, 2021)
The study aimed to identify the degree to which a sample of Palestinian university students in the southern governorates of Palestine appreciated the level of benefits that could be gained from new media in developing their security awareness, and its relationship to the study variables (sex - university - college).To achieve this, the descriptive analytical method was used by applying an electronic questionnaire that included (37) items distributed over (3) dimensions on a sample of (353) students of level four of (Al-Azhar University, Al-Quds Open University, and Israa University) who were selected from a total sample population of (4204) male and female students by the stratified random sampling method. The results showed that the overall assessment of the level of utilization of new media in developing security awareness from the viewpoint of the study sample was average. There were also no statistically significant differences at the level of (α ≤ 0.05) between the mean scores of the participants' responses regarding the level of benefit of new media in developing security awareness among university students in the southern governorates of Palestine attributed to all study variables (sex, university, college). The most used devices to benefit from the new media was mobile phone, which was mostly used for 3-6 hours a day, while social media networks (Facebook, Twitter) were the most preferred among the study participants. The study recommended creating a supportive legislative and cultural environment that would criminalize any negligence in the role of the media and educational institutions in the field of security awareness.